Design of Decision Support System in Selecting Cement Vehicles Based on Driver Performance, Expeditor Performance, and Waiting Time - Ihsan Prasetya; I Nyoman Pujawan (IPTEK Journal of Proceedings Series, 2019)
Current logistics developments affect a process in any company using third party logistics. Third party logistics is a distribution service, warehousing carried out by third parties (outsourcing). Third party logistics in its business practices has been owned by many parties. PT Z is one of the companies engaged in the cement industry which has a lot of cooperation with third party logistics. PT Z has assessed the expeditor partners. The problem that occurs is the problem of each driver and expeditor in the field agreeing to the same. There are some expeditors who have good performance and vice versa. In the midst of tight business third-party logistics resulted in each expeditor competing with each other and providing the best service to his clients. This research makes a decision support system by examining aspects that make the consideration of the selection of drivers and expeditors to be used for the transport of cement in PT Z. The method used in this study is the analytical hierarchy process (AHP) according experts’ opinion in cement industry. Research uses decision support systems based on web information systems as an application method. This research can determine the choice of the driver and expeditor who has the best performance to carry out the cement transportation process at PT Z by considering the driver's waiting time. Drivers who have better results will get greater opportunities (priority) chosen to transport cement